TRANSLATION STRATEGIES AND METHODS USED IN THE DEPARTMENT OF ENVIRONMENT AND FORESTRY - Masela Alifah; Indah Arvianti; Didit Kurniadi (Educational Tracker, 2023)
This research was based on translation problems due to the absence of equivalent words found during the translation process. Translators are required to translate the source language with the appropriate context into the target language. Therefore, researchers use translation strategies and methods to overcome these problems to produce the right equivalent. This study uses a qualitative method that focuses on applying translation strategies and methods. The data for this study was sourced from the official website and statistical books from the Department of Environment and Forestry, Central Java Province. The object of research is a collection of words or phrases that do not have a direct equivalent in the target language because they are non-equivalent and have limited expression in the target language. The results of this study indicate that the use of translation strategies and methods can support the translation process to be more effective and overcome translation problems. In the future, it is hoped that this finding will be able to contribute by increasing understanding for readers as well as providing references for translators on statistics and forestry topics.